Fe < 3 + > coordination photosensitive collagen bio-ink for DLP 3D printing, preparation method and application

By developing the FE3+coordinates of light -sensitive collagen biological ink, the problem of insufficient collagen mechanical properties and poor liquidity in DLP 3D printing, and realized the effective healing of diabetic wounds and the formation of blood vessels, showing good biological compatibility and accurate printing sex.

CN119367605APending Publication Date: 2025-01-28COLLAGEN (WUHAN) BIOTECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410654463.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively promote the healing of diabetic wounds, traditional treatment methods cannot effectively promote angiogenesis and accelerate tissue repair, and common materials have problems of insufficient mechanical performance and poor fluidity in DLP 3D printing.

Method used

Develop a FE3+coordinates of light -sensitive collagen biological ink, including 0.5 % to 1.5 % m/V methyl acrocylized collagen solution, 0.1 % ~ 0.5 % m/V light cause agent, 0 % ~ 0.5 % m/v UV absorbers and 0.005-0.5mg/ml Fe3+solution, through DLP 3D printing technology, prepare biological ink with good liquidity and mechanical properties.

Benefits of technology

This creature ink has higher mechanical performance, lower swelling ratio, better anti -degradation performance, can promote cell migration and proliferation, has good biocompatibility and accurate printability, suitable for preparing artificial skin, vascular, vascular, and vascular, vascular, and vascular, vascular, and vascular, and vascular, vascular, and vascular, and vascular, blood vessels,, blood vessels,, blood vessels,, blood vessels, blood vessels,, blood vessels, vascular,, vascular, blood vessels,, blood vessels, vascular, and vascular, vascular, and blood vessels. Smok and bone repair materials, especially in the treatment of diabetic wounds, show excellent healing effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367605A_ABST
    Figure CN119367605A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and relates to Fe < 3 + > coordination photosensitive collagen bio-ink for DLP 3D printing and a preparation method and application thereof.The bio-ink is prepared from 0.5%-1.5% m / v of a methacrylated collagen solution, 0.1%-0.5% m / v of a photoinitiator, 0%-0.5% m / v of an ultraviolet absorbent and 0.005 mg / mL-0.5 mg / mL of a Fe < 3 + > solution, the polymer has good flowability, printability, biocompatibility, degradation resistance and lower swelling property; the stent prepared by adding the active components can promote proliferation, migration and adhesion of human static umbilical vein endothelial cells (HUVECs) and enhance expression of angiogenesis related factors, and the HUVECs are helpful to form a stable vascular network; the dressing printed by utilizing the bio-ink loaded double cells with high biological activity has an excellent treatment effect on diabetic wounds, and has good clinical application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biomedical materials and relates to a Fe 3+ Coordinated photosensitive collagen bio-ink, preparation method and application. Background Art

[0002] The number of diabetes patients worldwide continues to grow and has exceeded 500 million, of which about 15% to 25% face the problem of difficult wound healing. Damage to microvessels and poor blood circulation caused by diabetes lead to a lack of oxygen and nutrient supply to the wound, immune system disorders increase the risk of infection, and nerve and vascular lesions affect the ability of wounds to repair. Current treatment strategies for diabetic wounds have limited effects. Commonly used methods such as debridement, hormones, and growth factor therapy have failed to effectively address the adverse effects of a high blood sugar environment on wound healing, and long-term use of antibiotics can easily lead to drug resistance. Traditional treatments are also unable to effectively promote angiogenesis and accelerate tissue repair, and there is an urgent need to develop new treatment strategies to address these challenges.

[0003] 3D printing is an advanced manufacturing technology that uses computer-aided design to generate 3D models. It can be used to print biomaterials such as cells, bioactive molecules and scaffolds to build biocompatible and functional tissue engineering structures. The most commonly used 3D printing technologies are inkjet, extrusion and photocuring. Among them, the material for inkjet printing must be in liquid state and require low viscosity. Bio-ink with high cell viscosity will cause clogging of the nozzle head; extrusion bioprinting can achieve the printing of high-viscosity materials, but too high viscosity will limit cell diffusion, migration and proliferation; photocuring printing achieves three-dimensional preparation of parts by selectively curing photosensitive polymers layer by layer, including stereolithography (SLA), digital light processing (DLP) and micro-stereolithography (MSL). DLP has the characteristics of high resolution, good intensity uniformity and high precision, and is suitable for biocompatible materials. It is widely used in the biomedical field.

[0004] The preparation of bio-ink is the core link in DLP 3D printing technology. The bio-ink used for DLP 3D printing needs to meet the requirements of printability, degradability and good biological activity. Collagen, as the most abundant protein in the human body, constitutes the main part of the extracellular matrix and provides structural support for various tissues and organs. Due to its excellent biological activity, low immunogenicity and excellent biodegradability, collagen has been widely used in the field of tissue engineering. However, in the application of DLP 3D printing technology, collagen faces challenges caused by its poor water solubility and limited mechanical strength. Summary of the invention

[0005] In view of the above technical problems, the object of the present invention is to provide a Fe for DLP 3D printing. 3+ The photosensitive collagen bio-ink comprises the following components: 0.5% to 1.5% m / v methacryloyl collagen solution, 0.1% to 0.5% m / v photoinitiator, 0% to 0.5% m / v UV absorber and 0.005-0.5 mg / mL Fe 3+ Solution.

[0006] Preferably, the collagen is bovine collagen.

[0007] Preferably, the bovine collagen is type I bovine collagen, and / or type II bovine collagen, and / or type II bovine collagen.

[0008] Preferably, the photoinitiator includes one or more of LAP, TPO, and I2959.

[0009] Preferably, the photoinitiator is LAP.

[0010] Preferably, the ultraviolet absorber includes one or more of lemon yellow and food coloring brilliant blue.

[0011] Preferably, the ultraviolet absorber is lemon yellow.

[0012] The second object of the present invention is to provide a method for preparing the bio-ink, comprising the following steps:

[0013] (1) dissolving freeze-dried collagen sponge in acetic acid solution to prepare collagen solution, and slowly stirring to dissolve;

[0014] (2) adding methacrylic anhydride dropwise to the collagen solution obtained in step (1), adjusting the pH to maintain at 4-7, reacting at low temperature for 24 hours, dialyzing, and freeze-drying to obtain methacrylylated collagen;

[0015] (3) Prepare 0.5% to 1.5% m / v methacrylated collagen solution with acetic acid solution, add sodium hydroxide solution to adjust the pH of the solution to neutral, add 0.1% to 0.5% m / v photoinitiator, 0% to 0.5% m / v UV absorber and 0.005-0.5 mg / mL Fe 3+ The solution was mixed evenly and centrifuged to remove bubbles to obtain CMA / Fe 3+ Bio-ink.

[0016] The third object of the present invention is to provide the use of the biological ink in the preparation of artificial skin, artificial blood vessels, cartilage and bone repair materials, corneal transplant materials, hemostatic materials, drug sustained release, drug delivery, tissue engineering and wound dressings.

[0017] The fourth object of the present invention is to provide a dressing for treating diabetic wounds, wherein the dressing is obtained by adding active ingredients to the bio-ink and printing it through DLP 3D.

[0018] Preferably, the active ingredients are not limited to cells, drugs or other active ingredients.

[0019] The fifth object of the present invention is to provide the use of the dressing in preparing the treatment of diabetic wounds.

[0020] The present invention has the following beneficial effects: (1) The present invention provides a Fe for DLP 3D printing 3+ Coordinated photosensitive collagen bio-ink, preparation method and application, the bio-ink comprises the following components: 0.5% to 1.5% m / v methacryloyl collagen solution, 0.1% to 0.5% m / v photoinitiator, 0% to 1.0% m / v ultraviolet absorber and 0.005-0.5 mg / mL Fe 3+ The solution has good fluidity, higher mechanical properties, lower swelling ratio, better anti-degradation performance; it also has the ability to promote cell migration, the performance of promoting cell proliferation, good biocompatibility, and precise printing performance;

[0021] (2) The PCMA-Fe bio-ink prepared by adding angiogenesis-promoting polypeptides to the bio-ink of the present invention has excellent printability and precision, stronger biological activity, higher biocompatibility, and higher cell survival rate; encapsulating HUVECs cells in the PCMA-Fe bio-ink for printing can effectively promote the proliferation of HUVECs cells in the gel. At the same time, the gel printed with PCMA-Fe ink can promote the migration of HUVECs, and stimulate HUVECs to express angiogenesis-related factors (such as VEGF, vWF, CDH5, etc.), accelerate the speed of HUVECs forming blood vessels, and help HUVECs form a stable vascular network.

[0022] (3) The artificial skin prepared by the PCMA-Fe bio-ink loaded with human fibroblasts (HDFs) and HUVECs cells, after 14 days of culture, the gel still maintained good structural integrity, and the cells in the gel proliferated significantly, with a very high cell survival rate. It is applied to the treatment of diabetic wounds, can promote wound healing, has excellent therapeutic effects, and has good clinical application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Fe 3+ The coordination concentration screening diagram;

[0024] Figure 2 CMA-Fe 3+ Circular dichroism characterization of (CMA-Fe);

[0025] Figure 3 Characterization of the cross-linking mechanism of CMA-Fe.

[0026] Note: a. IR spectra of CMA and CMA-Fe; b. XPS full spectra of CMA and CMA-Fe; c. N element fine spectrum of CMA-Fe; d. O element fine spectrum of CMA-Fe;

[0027] Figure 4 Printability and gel property characterization of CMA-Fe.

[0028] Note: a. Schematic diagram of the double cross-linked network of CMA-Fe bio-ink; b. Schematic diagram of DLP 3D printing; c. Immediate image of the printed frustum with protruding ribs; d. CAD model of the frustum with protruding ribs and pictures at different angles after printing and dyeing; f. CAD model of a 4 cm high three-dimensional rabbit, pictures immediately after printing and after secondary curing; g. CAD model of a 3.5 cm long leaf, pictures immediately after printing and after secondary curing; h. Compression stress-strain curves of CMA and CMA-Fe; i. Compressive elastic modulus of CMA and CMA-Fe under different strains; j. Swelling curves of CMA and CMA-Fe; k. The mass residual percentage of CMA and CMA-Fe in collagenase solution.

[0029] Figure 5 Biocompatibility of CMA-Fe bioink.

[0030] Note: a. Cell migration 24 hours after CMA and CMA-Fe treatment; b. Relative cell proliferation rate after 1, 3, and 5 days of CMA and CMA-Fe treatment; ce. Live and dead cell staining of cell encapsulation in CMA-Fe ink; fh. Live and dead cell staining of cell-printed grids loaded with CMA-Fe ink.

[0031] Figure 6 Construction and bioactivity characterization of PCMA-Fe bioink.

[0032] Note: a. Schematic diagram of the design of PCMA-Fe bio-ink with enhanced bioactivity; b. Printability of PCMA-Fe ink: taking the octopus model with 8 tentacles as an example; c. 2D culture (Blank), cytoskeleton staining of fibroblasts grown on CMA, CMA-Fe and PCMA-Fe gels for 3 days; d. Absorbance (OD) of endothelial cells (HUVECs) encapsulated with CMA, CMA-Fe and PCMA-Fe bio-inks at 1, 4 and 7 days 450nm); e. Cell migration of untreated (Blank), CMA, CMA-Fe and PCMA-Fe treated HUVECs after 19h; f. Cell migration rate of untreated (Blank), CMA, CMA-Fe and PCMA-Fe groups; g. Relative expression rate of VEGF in untreated (Blank), CMA, CMA-Fe and PCMA-Fe treated HUVECs; h. Relative expression rate of VACM in untreated (Blank), CMA, CMA-Fe and PCMA-Fe treated HUVECs 1; i. The relative expression rate of PECAM-1 in untreated (Blank), HUVECs treated with CMA, CMA-Fe and PCMA-Fe; j. The relative expression rate of vWF in untreated (Blank), HUVECs treated with CMA, CMA-Fe and PCMA-Fe; k. The relative expression rate of CDH5 in untreated (Blank), HUVECs treated with CMA, CMA-Fe and PCMA-Fe.

[0033] Figure 7 PCMA-Fe bio-ink promotes HUVECs angiogenesis;

[0034] Note: a. Tube formation of Blank (no drug treatment), CMA, CMA-Fe and PCMA-Fe treated HUVECs on Matrigel (2h), the pictures were processed by Image J software; b. Tube formation of Blank (no drug treatment), CMA, CMA-Fe and PCMA-Fe treated HUVECs on Matrigel (6h); c. Number of nodes in Blank, CMA, CMA-Fe and PCMA-Fe groups; d. Number of lumens in Blank, CMA, CMA-Fe and PCMA-Fe groups; e. Number of branch points in Blank, CMA, CMA-Fe and PCMA-Fe groups; f. Number of branch points in Blank, CMA, CMA-Fe and PCMA-Fe groups; Total branch length in Blank, CMA, CMA-Fe and PCMA-Fe groups.

[0035] Figure 8 Cell-laden printing performance of PCMA-Fe bio-ink.

[0036] Note: a. Schematic diagram of PCMA-Fe ink cell printing; b. Fibroblast grid immediately after printing; c. Live and dead cell staining of fibroblast grid; d. Local magnification of grid; e. Fusion of printed grid and CAD model; f. Donkey model, heart model, five-pointed star model and leaf model printed with fibroblasts; g. Cell survival rate of cell printing; h. CAD model of ear model printed with endothelial cells, immediately after printing and pictures of force compression and recovery after 1 hour of culture; i. Cell proliferation of a single mesh of endothelial cell printed grid on days 1, 4, 7 and 12; j. Quantitative analysis of cell proliferation of a single mesh of endothelial cell printed grid on days 1, 4, 7 and 12; k. Picture of endothelial cell printed grid on day 15 and 3D images from different angles; l. Picture of endothelial cell printed grid fused with CAD model on day 15.

[0037] Fig. 9 Design and characterization of dual-cell artificial skin;

[0038] Note: a. Design drawing of a 9mm long and 2.5mm high double-cell artificial skin; b. Actual picture of artificial skin cultured in vitro for 14 days after printing; c. Migration of double cells with different stains at 3h; d. Migration of double cells with different stains at 24h; e. Live and dead cell staining of upper cells after 14 days of culture; f. Live and dead cell staining of lower cells after 14 days of culture. Fig.10 Diabetic wound healing research. DETAILED DESCRIPTION

[0039] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings of the specification. Obviously, the described embodiments are only a part of the present invention, not the whole of the invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] In the following examples, unless otherwise specified, the methods used are all conventional methods;

[0041] In the following examples, unless otherwise specified, the reagents used are conventional reagents that can be purchased from the market.

[0042] In the embodiment of the present invention, yak type I collagen is used as raw material (for the extraction method, see invention patent CN113520900B) for DLP 3D printing collagen bio-ink, but the present invention is not limited to bovine collagen, and collagen obtained by any other means may be used, including type I collagen, type II collagen, type III collagen, etc.

[0043] In the following embodiments, the collagen DLP 3D printing bio-ink is called bio-ink before printing and is called hydrogel after DLP 3D printing.

[0044] Example 1: CMA-Fe 3+ (CMA-Fe) coordination cross-linking study

[0045] 1.Fe 3+ Concentration screening of liganded CMA

[0046] Use 0.5M acetic acid at low temperature to dissolve collagen solid to 4mg / mL. Add sufficient methacrylic anhydride (MA) dropwise to the stirred collagen solution. Slowly add high concentration NaOH to adjust the pH and keep it at 4-7. After reacting for 24 hours under low temperature stirring, place the reaction solution in a macromolecular dialysis bag and dialyze until no MA remains. The CMA solution after the reaction is freeze-dried to obtain CMA solid.

[0047] Screening of Fe using 0.5% CMA neutral solution 3+ FeCl3 was dissolved into a 10 mg / mL stock solution. FeCl3 was added to CMA to a final concentration of 0.005, 0.01, 0.05, and 0.5 mg / mL, and mixed thoroughly. After vigorous shaking, it was inverted on the table to observe the gelation of the CMA-Fe solution.

[0048] The results are as follows Figure 1 As shown, CMA and 0.5 mg / mL Fe 3+ After the reaction, a gel was formed quickly, indicating that CMA and Fe 3+ There is a cross-linking reaction between them. CMA is a photosensitive collagen. After adding an initiator, it can be cured under ultraviolet light or blue light, which meets the ink requirements of DLP 3D printing. However, due to the poor mechanical properties of collagen and insufficient support, its 3D printing formability is poor. Therefore, CMA and Fe 3+ Mixing has the potential to improve the mechanical properties of CMA to further improve printability. However, DLP 3D printing bio-ink needs to have good fluidity to ensure printing accuracy. Therefore, CMA / Fe 3+ The solution needs to be Fe-free while ensuring good fluidity. 3+ Concentration selection. 3+ CMA can be cross-linked to form a gel within 1 minute, which affects the fluidity of CMA and makes subsequent 3D printing impossible. 3+ The concentration was controlled below 0.5 mg / mL.

[0049] 2. Circular dichroism (CD) characterization

[0050] For 1mg / mL CMA and CMA-Fe (containing 0.05mg / mL Fe 3+ ) solution was characterized by circular dichroism. The samples were equilibrated at 4 °C for at least 24 h before CD measurement. A cell with a path length of 1 mm was used. The wavelength was scanned from 180 to 260 nm with a step increment of 1.0 nm and an averaging time of 1.0 s.

[0051] The results are as follows Figure 2 As shown in Figure 2, CMA shows a negative peak at 198nm and a positive peak at 222nm, indicating that CMA has a typical collagen triple helix structure. Similarly, CMA-Fe solution also showed similar negative and positive peaks at 198nm and 222nm, indicating that Fe 3+ The addition of did not affect the triple helical structure of CMA.

[0052] 3. Study on coordination mechanism

[0053] The CMA and CMA-Fe inks were freeze-dried and thin sheets were made by potassium bromide tableting method to measure their FTIR spectra to analyze the characteristic absorption peaks. The solidified CMA and CMA-Fe gels were freeze-dried and their X-ray photoelectron spectroscopy (XPS) was measured to analyze the elemental composition. The fine spectra of N and O elements were further characterized to analyze the interaction.

[0054] The results are as follows Figure 3 As shown in the FT-IR spectrum, CMA is -1 The absorption peak at 3387 cm-1 in CMA-Fe is blue-shifted to 3387 cm-1. -1 , while at 1654cm -1 The vibration peak at 1641 cm-1 in CMA-Fe is significantly shifted to 1641 cm-1. -1 ( Figure 3 a) These results indicate that the iron ions coordinate with the -NH2 and -COOH groups of CMA. XPS wide scan spectrum analysis shows that O1s, N 1s and C1s peaks exist in both CMA and CMA-Fe, while Fe 2p 3 / 2 The characteristic peaks of can only be detected in CMA-Fe ( Figure 3 b). The N1s core level spectrum of CMA-Fe shows peaks at binding energies of 399.8 eV and 400.5 eV, proving the existence of Fe-N bonds ( Figure 3 c). Similarly, the O1s core spectrum of CMA-Fe shows peaks at 531.4 eV and 532.0 eV, further confirming the existence of Fe-O bonds ( Figure 3 d) These results indicate that the cross-linking between CMA and iron ions is achieved through the coordination of -COOH and -NH2 groups of collagen.

[0055] Example 2 Preparation of CMA-Fe Bio-ink

[0056] According to the ink formula in Table 1, 12 kinds of bio-inks were prepared, in which the concentration of CMA solution was 0.5% to 1.5% m / v, Fe 3+ The concentration is 0.005-0.5 mg / mL, the photoinitiator concentration is 0.1%-0.5% m / v, and the UV absorber concentration is 0%-0.5% m / v. Most of the bio-inks prepared within this range conform to the mechanism of DLP 3D printing. Therefore, bio-inks not limited to these 12 formulas can be prepared according to different application requirements.

[0057] Bio-inks 1-4 were studied with different Fe 3+ Effect of concentration on ink system. Bio-ink 1-3 has good fluidity and meets the requirements of DLP 3D printing. Bio-ink 4 can form a coordinated cross-linked gel within 1 minute, which affects the fluidity of the ink and is not suitable for printing. 3+ The concentration is the preferred concentration, taking into account the improvement of mechanical properties and cell-carrying biocompatibility. Therefore, this formula is used in the printability of CMA-Fe bio-ink and gel characterization. Bio-ink 5-9 uses 1.0% CMA, and the effect of different concentrations of photoinitiator on the system is studied. The increase in CMA concentration can further enhance the cross-linking density of the gel, thereby improving the performance of the gel, which is conducive to the application of tissue engineering. All five formulations can be printed, but the printing parameters need to be adjusted and the printing quality varies. In addition, due to the small amount of photoinitiator in bio-ink 5, the reaction time needs to be extended, and the printing time is longer, so this formula is not used. Considering the cytotoxicity of the photoinitiator, bio-ink 7-9 is not used when printing with cells. Therefore, bio-ink 6 is used when printing with active ingredients or cells in the subsequent addition. Bio-ink 10-12 can be cured, but the CMA concentration used is high, the viscosity is large, and the printing accuracy is low. Among them, bio-ink 10 has no UV absorber, is easy to overexpose during printing, has low printing accuracy, and is limited to printing simple plane models. Bio-inks 11-12 contain more UV absorbers, which can improve printing accuracy, but usually require a long printing time. Therefore, bio-inks 11-12 are usually not used when printing complex three-dimensional models. Since there are many variables in the bio-ink formula, the flexibility of adjustment is extremely high. Therefore, by adjusting within the range listed in this article, a series of bio-inks with high biocompatibility and high-precision printing can be obtained.

[0058] Table 1 Formulations of different bio-inks

[0059]

[0060] Example 3 Printability and gel properties of CMA-Fe bio-ink

[0061] The rheological properties of the hydrogels were analyzed using an Anton Paar rheometer. After in-situ curing of the freshly prepared CMA and CMA-Fe, the rheological properties of the hydrogels were analyzed using a parallel plate and a portable curing light source (wavelength 405 nm, light intensity 25 mW / cm 2 ) was subjected to a 70-second time scanning oscillation, and its storage modulus (G') and loss modulus (G") (γ=1%, ω=1rad / s, gap 0.7mm) were detected. Different 3D models were successfully printed using a DLP 3D printer using a bio-ink composited with 0.5% CMA and iron ions, including a 2cm diameter truncated cone with protruding ribs, a 4cm high rabbit, and a 3.5cm long leaf. The printed truncated cone was photographed and its structure was observed at different angles. At the same time, the blue-dyed truncated cone was photographed after secondary curing. The rabbit and leaf models were photographed immediately after printing and secondary curing, respectively. The swelling and anti-degradation properties of CMA and CMA-Fe gels were characterized. 10mm×10mm cylinders were printed using CMA and CMA-Fe inks, and the stress-strain curve of the hydrogel was tested using a universal testing machine (displacement rate 20mm / min, strain 0-50%).

[0062] The results are as follows Figure 4 As shown, CMA-Fe bio-ink successfully achieved 0.5% collagen printing by forming a double cross-linked network ( Figure 4 a). Using a DLP 3D printer, a 2cm diameter truncated cone with protruding ribs was printed. The truncated cone had a complete three-dimensional structure immediately after printing ( Figure 4 c), after secondary curing and dyeing, the complete structure and uniform ridges were more clearly observed at different angles ( Figure 4 d). This indicates that the dual cross-linking strategy successfully achieved DLP printing of low-concentration CMA. The in-situ curing results show that the dual cross-linked CMA-Fe ink can reach a storage modulus that is 2 times higher than that of CMA within 10 seconds, and finally obtain a storage modulus that is significantly higher than that of CMA ( Figure 4 e). This enables the CMA-Fe ink to achieve sufficient mechanical strength within a limited light intensity and exposure time during the printing process, thus having sufficient support, thus achieving successful printing of low-concentration collagen. In addition, a rabbit with a height of 4 cm was successfully printed using CMA-Fe ( Figure 4 f) and a leaf model with a length of 3.5 cm ( Figure 4 g). UA is added during printing to improve printing accuracy. After printing, the gel is yellow (the color of UA), so secondary curing is required after printing to further complete the reaction (the gel is colorless or translucent at this time).

[0063] The properties of CMA-Fe gel were further characterized by compression, swelling and anti-degradation tests. Compared with CMA, CMA-Fe gel has higher compressive strength under different strains, indicating that the double-crosslinked CMA-Fe gel has stronger mechanical properties than the single-crosslinked CMA gel ( Figure 4 h, i). CMA-Fe has a lower swelling ratio, which is due to the larger cross-linking density of CMA-Fe gel ( Figure 4 j). In addition, CMA-Fe retained more mass in collagenase over time, indicating that the CMA-Fe gel degraded more slowly. These results all indicate that the double cross-linking strategy helps low-concentration CMA improve mechanical properties, thereby achieving the successful preparation of collagen-based DLP 3D printing bio-ink with structural integrity and printability.

[0064] Example 4 Cell-carrying biocompatibility of CMA-Fe bio-ink

[0065] Cell migration assay: The solidified CMA and CMA-Fe gels were washed 3 times with 1×PBS and then immersed in DMEM basal medium for 24 hours. The gel extracts of CMA and CMA-Fe were collected. The confluent L929 cells were digested into pretreated 6-well plates and cultured with complete medium for 24 hours. The confluent cells were streaked with a 10μL pipette tip and then washed 3 times with 1×PBS. The gel extracts of CMA and CMA-Fe were added and bright field images were taken under an inverted microscope at 0 hours and 24 hours.

[0066] Cell proliferation assay: L929 cells (1×10 5 cells / mL) and cultured for 24 hours. After removing the culture medium, wash with 1×PBS three times, and then add CMA and CMA-Fe gel extracts. DMEM was added to the Blank group as a blank control, and 6 replicates were set up in each group. After 1 day, 3 days and 5 days of culture, the extract and DMEM were removed, and CCK-8 working solution diluted with DMEM was added. After incubation in the dark for 1 hour, the absorbance at 450nm was measured using an enzyme reader. After deducting the absorbance of cell-free DMEM, the relative growth rate of different groups was calculated.

[0067] Cell encapsulation experiment: L929 cells were digested to prepare a high-concentration cell suspension (about 1×10 7cells / mL). Pipette 100μL of cell suspension into 1mL of sterile CMA-Fe ink and mix quickly to avoid bubbles. Pipette 250μL of CMA-Fe bio-ink containing cells into a 15mm diameter laser confocal dish and cure it under 405nm UV light for 30 seconds. Wash three times with the finished culture medium quickly and add fresh finished culture medium to culture for 1 day. Stain the cell-laden gel for live and dead cells and observe the cell survival under a laser confocal microscope. Turn on the Z axis when shooting.

[0068] Cell-carrying printing experiment: Add the cell-carrying CMA-Fe bio-ink into the ink tank of the DLP printer, and print the grid according to the default slicing parameters and the pre-adjusted printing parameters. Immediately after printing, put the grid into the culture medium and place it under UV light for secondary curing to ensure full reaction. Then replace the culture medium, place it in the cell culture incubator for 1 day, and then image it under laser confocal. When shooting, turn on the Z-axis shooting and superimpose the Z-axis images.

[0069] The results are as follows Figure 5 As shown in Figure 2, compared with CMA, cells treated with CMA-Fe gel extract migrated more to the center of the scratch after 24 hours, indicating that CMA-Fe has the ability to promote cell migration ( Figure 5 a). At the same time, compared with the first day (Day 1), the cells under the treatment of CMA-Fe group had a faster cell proliferation rate, which was significantly higher than that of the CMA group on the third day (Day 3) and the fifth day (Day 5), indicating that CMA-Fe has the performance of further promoting cell proliferation ( Figure 5 b). The cell encapsulation experiment further characterized the compatibility of CMA-Fe bio-ink with cells. The live-dead cell staining results showed that almost all the cells inside the gel were green 24 hours after encapsulation, indicating that the cells were alive ( Figure 5 c). Larger multiples ( Figure 5 d) and in 3D view ( Figure 5 e) cells are uniformly distributed and viable, indicating that CMA-Fe bio-ink has good biocompatibility. The cell-carrying printing results verify the cell-carrying printability of CMA-Fe bio-ink and further verify the biocompatibility. The results show that CMA-Fe can print micron-scale grid structures ( Figure 5 f). Further magnification of the cross ( Figure 5 g) and individual meshes ( Figure 5 h) all show clear outlines, indicating the precise printing pattern of CMA-Fe bio-ink when printing cells. At the same time, all cells are green, with almost no red cells, illustrating the superior biocompatibility of CMA-Fe as a bio-ink.

[0070] Example 5 Construction and bioactivity characterization of PCMA-Fe bio-ink

[0071] Preparation and printing of PCMA-Fe ink: Prepare a sterile CMA solution, add angiogenic peptides filtered through a 0.22 μm filter membrane (final concentration of 0.5 mg / mL, sequence QHREDGS, purchased from Hefei Xingpeptide Biotechnology Co., Ltd.), and mix thoroughly. Then add FeCl3 filtered through a 0.22 μm filter membrane (final concentration of 0.05 mg / mL) and shake quickly. According to the subsequent experimental arrangement, LAP and UA (only when printing) were added, and then centrifuged to remove bubbles (4000 rpm, 5 min). Use PCMA-Fe ink to print an octopus model with 8 tentacles, a height of 2 cm, and a width of 2.8 cm by DLP 3D printing.

[0072] Cell adhesion experiment: Sterile inks of CMA, CMA-Fe and PCMA-Fe were prepared and cured for 30 seconds to obtain a smooth surface gel. L929 cells were digested to obtain a high-concentration cell suspension (about 1×10^6 cells / mL), 100 μL of cell suspension was added to each gel surface, and after overnight culture, the cells were completely adhered to the gel, and then complete medium was added for 3 days. The cytoskeleton and nucleus were stained with phalloidin and Hoechst 33342, and the images were observed under a laser confocal microscope.

[0073] HUVECs cell encapsulation experiment: Prepare sterile inks of CMA, CMA-Fe and PCMA-Fe. Add 100 μL of HUVECs cell suspension (about 1×10^6 cells / mL) to 1 mL of ink, mix thoroughly, and then pipette 100 μL / well into the pretreated 96-well plate, and then cure under 405 nm UV light for 30 seconds. Set up 6 replicate wells for each group. After curing, wash the gel, add fresh culture medium and culture in a cell culture incubator. Replace the culture medium every two days, remove the culture medium on the 1st, 4th and 7th days, add 100 μL of diluted CCK-8 working solution, and measure the absorbance at 450 nm under an ELISA reader.

[0074] HUVECs cell migration experiment: The solidified CMA, CMA-Fe and PCMA-Fe gels were washed three times with 1×PBS, and then soaked in DMEM basal medium for 24 hours to obtain gel extract. 90% confluent HUVECs cells were digested and added to the pretreated 6-well plate and cultured for 24 hours. The cells were streaked with a 10μL pipette tip, and then bright field images of the cell scratches were taken under an inverted microscope at 0 hours and 19 hours. Image J software was used to calculate the cell migration rate.

[0075] RT-qPCR experiment of HUVECs: HUVECs were cultured at 5×10 5 The cells were plated at a density of 10 cells / mL in a pretreated 6-well plate. After 24 hours of adhesion, the culture medium was removed and the gel extracts of CMA, CMA-Fe and PCMA-Fe were added. On the 4th and 7th days, total RNA in the cells was extracted using an RNA isolation kit, and the concentration and purity of the RNA samples were determined using a NanoDrop spectrophotometer. cDNA was synthesized using a PrimeScript RT kit with gDNAEraser, and then the expression levels of genes were detected using TB GreenPremix Ex Taq II. The GAPDH gene was used as an internal reference gene for normalization, and the relative expression levels of angiogenesis-related genes were calculated by the 2^(-ΔΔCT) method.

[0076] Table 2 Primer sequences used for RT-qPCR

[0077]

[0078] The results are as follows Figure 6 As shown, CMA-Fe 3+ -Pro-angiogenic peptide (PCMA-Fe) composite bio-ink ( Figure 6 a) and conducted DLP 3D printing verification. Figure 7 As shown in Figure 2b, the ink successfully replicated an octopus model with eight tentacles, demonstrating excellent printability and accuracy. Immunofluorescence staining was then performed on cells adhering and proliferating on CMA, CMA-Fe, and PCMA-Fe gels ( Figure 6 c). The results showed that compared with 2D culture, the cells in 3D culture further proliferated in the gel and showed a spreading fibrous shape. It is particularly noteworthy that the cell confluence on the PCMA-Fe gel was higher, indicating that PCMA-Fe has stronger biological activity. The proliferation of HUVECs cells encapsulated in the gel was further analyzed ( Figure 6 d). The results showed that the OD value of HUVECs cells in the PCMA-Fe group was the highest, indicating that PCMA-Fe can effectively promote the proliferation of HUVECs cells in the gel. In addition, cell migration experiments were also performed ( Figure 6 e), it was found that the HUVECs cells treated with PCMA-Fe migrated to the scratch site significantly faster than those in other groups within 19 hours, reaching almost 100% cell confluence ( Figure 6 f). Finally, the effect of PCMA-Fe on the expression of angiogenesis-related growth factors (VEGF, vWF, VCAM-1, PECAM-1 and CDH5) was analyzed ( Figure 6gk). The results showed that compared with the untreated blank group (Blank), CMA, CMA-Fe and PCMA-Fe could significantly promote the expression of these growth factors in HUVECs cells, among which PCMA-Fe had a significantly higher promoting effect on these five growth factors than CMA and CMA-Fe. This indicates that the constructed PCMA-Fe has superior biological activity and potential to promote angiogenesis. These results strongly demonstrate the significant effect of PCMA-Fe composite bio-ink in promoting angiogenesis, including enhancing cell proliferation, promoting cell migration, and improving growth factor expression.

[0079] Example 6 PCMA-Fe bio-ink promotes HUVECs angiogenesis

[0080] Matrigel was taken out from -20℃ and melted at 4℃ overnight. Centrifuge tubes, pipette tips, DMEM culture medium and 96-well plates were pre-cooled in advance. The melted matrix gel was mixed and diluted with DMEM at a ratio of 1:2, and then added vertically to the pre-cooled 96-well plate at a volume of 50μL / well to avoid bubbles. HUVECs (P4-P6) with a confluence greater than 80% were digested and centrifuged, and the cell concentration was calculated using a hemocytometer, and 20,000 cells were added to each well. CMA, CMA-Fe, and PCMA-Fe gel extracts were added with the cells, and a Blank control group without drug treatment was set up, with 3 parallel wells in each group. After the cells and drugs were added, they were placed in a cell culture incubator, and the angiogenesis was observed every hour. At 2 hours and 6 hours, imaging was performed using an inverted fluorescence microscope. The tube-forming images after 2 hours were converted into 8-bit-RGB color using Image J and analyzed using Angiogenesis Analyzer. The data of Number of nodes, Number of tubes, Number of junctions and Total branching length were plotted to quantitatively analyze the angiogenesis.

[0081] The results are as follows Figure 7 As shown in Figure 2, HUVECs in the Blank group did not form an obvious reticular structure within 2 hours, while HUVECs in the CMA, CMA-Fe, and PCMA-Fe groups had formed a vascular network ( Figure 7 a). In particular, almost all cells in the PCMA-Fe group were connected to the vascular network and formed more meshes. This indicates that PCMA-Fe treatment can accelerate the rate of HUVECs forming blood vessels. Quantitative analysis of the vascularization network further confirmed this result. PCMA-Fe-treated cells had more vascular nodes, tubes, and junctions within 2 hours, and also showed a longer total vascular branch length ( Figure 7 cf). Compared with the CMA and CMA-Fe groups, the angiogenesis ability of the PCMA-Fe group was significantly enhanced. In addition, after 6 h, the PCMA-Fe group formed the most uniform and stable lumen ( Figure 7 b). In summary, PCMA-Fe treatment promoted the angiogenesis rate of HUVECs, implying the successful construction of collagen-based 3D printing ink with pro-angiogenic ability.

[0082] Example 7 Cell-carrying printing performance of PCMA-Fe bio-ink

[0083] Human dermal fibroblasts (HDFs) were cultured to 90% confluence and then digested and centrifuged to obtain a high-concentration cell suspension (about 2×10^7cells / mL). 100μL of cell suspension was added to each 1mL of sterile PCMA-Fe bio-ink, mixed and added to the printer ink tank, and then grid, donkey, heart, five-pointed star and leaf models were printed according to the preset parameters. After printing, the sample was immediately placed in the finished culture for secondary curing and washed. After replacing the fresh culture medium, the sample was placed in the incubator and cultured for 24 hours. The printed gel was stained with a live and dead cell staining kit and then observed and imaged under a confocal laser scanning microscope (CLSM). Similarly, human umbilical vein endothelial cells (HUVECs) were cultured to 80%-90% confluence and then digested and centrifuged to obtain a high-concentration cell suspension (about 1×10^7cells / mL). 100 μL of cell suspension was added to each 1 mL of sterile PCMA-Fe bio-ink, mixed and added to the printer ink tank, and then the grid and ear model were printed according to the preset parameters. After the ear loaded with cells was immersed in the finished culture for secondary curing, pressure was applied to compress the gel, and then released, and the gel images before, during and after compression were recorded. For the grid loaded with cells, samples were taken out after 1, 4, 7, 12 and 15 days of culture, and the printed gel was stained with a live and dead cell staining kit, and then observed and imaged under CLSM. Image J software was used to calculate the cell viability of HDFs on the first day and the cell viability of HUVECs on the 12th day. At the same time, Image J was used to count the live cells of a single grid carrying HUVECs on days 1, 4, 7 and 12. Finally, the CAD models of the grids loaded with HDFs and HUVECs were fused with the images taken by CLSM using Photoshop software to evaluate the printing accuracy and cell distribution.

[0084] The experimental results are as follows Figure 8 After mixing cells with PCMA-Fe bio-ink, cell-loaded ink was obtained, and various 3D models were successfully printed by DLP ( Figure 8a). The mesh immediately after printing with HDFs shows clear mesh and edge contours ( Figure 8 b). After 24 hours of culture, the HDFs grid under CLSM imaging showed evenly distributed green fluorescent cells, and the image under magnification showed very few dead cells (red), indicating that most of the printed cells survived ( Figure 8 c). Further magnification of the grid revealed that the printed grid had micron-level printing accuracy ( Figure 8 d). The fusion of the CAD model and the CLSM image further confirmed that the cells were evenly distributed within the preset and printed lines, indicating that the addition of cells had little effect on the printing accuracy ( Figure 8 e). In addition, green cells are evenly distributed in the printed donkey, heart, five-pointed star and leaf models ( Figure 8 f), the details of each model are clearly visible, including the donkey's ears (especially the inserted bright field image), the sharp corners of the five-pointed star, and the veins of the leaves. Although it is a 2D image, the 3D sense of the heart-shaped model is still visible. By cell counting, it was found that the cell survival rate was as high as 94.24±0.7% ( Figure 8 g), verifying the high biocompatibility of PCMA-Fe loaded cell printing.

[0085] The feasibility of printing PCMA-Fe loaded HUVECs was also studied. The ear model immediately after printing showed a complete structure and was able to recover its original shape after applying pressure, indicating the feasibility of printing loaded HUVECs ( Figure 8 h). In the printed grids, HUVECs showed significant cell proliferation on days 1-12 ( Figure 8 i), further quantitative analysis showed that HUVECs proliferated significantly within the printed gel ( Figure 8 j), which indicates that PCMA-Fe bio-ink provides a good 3D growth environment for cells and promotes cell proliferation. The HUVECs cell survival rate reached 93.9±0.49% on the 12th day, further confirming the high biocompatibility of PCMA-Fe bio-ink ( Figure 8 g). In addition, we analyzed the meshes 15 days after printing and found that the cell-loaded printed meshes still maintained good structural integrity after 15 days of culture ( Figure 8 k). The 3D image further demonstrates the uniform distribution of living cells within the gel. Figure 8 After the mesh was fused with the CAD model, it was found that the mesh still matched the model well after 15 days of printing, which fully demonstrated the potential of PCMA-Fe as a tissue engineering bio-ink. These results show that PCMA-Fe cell-loaded ink has good printability and high cell survival rate, providing broad prospects for applications such as artificial tissue construction.

[0086] Example 8 Design and Characterization of Dual-Cell Artificial Skin

[0087] An artificial skin model with a diameter-to-height ratio of 9:2.5 was designed using 3D modeling software, including a hollow circular tube in the bottom layer, a square hollow in the middle layer, and a solid layer in the top layer. These three layers together form a cylindrical model. In order to mimic the tissue structure of human skin, HUVECs cells were loaded in the bottom layer, and HDFs cells were loaded in the middle and top layers. First, sterile PCMA-Fe bio-ink was prepared, and HDFs were added to prepare cell-loaded ink 1, with a cell density of approximately 1×10^6cells / mL. Then, HUVECs were added to sterile PCMA-Fe bio-ink to prepare cell-loaded ink 2, with a cell density of approximately 5×10^5cells / mL. The printing parameters were set to a layer height of 25μm, an exposure time of 16 seconds, and a light intensity of 15mW / cm^2. First, ink 1 was added to the ink tank to print the bottom layer and the middle layer. When printing was completed, ink 1 in the ink tank was paused and cleaned, and then ink 2 was added to continue printing the remaining bottom layer. After printing, the artificial skin was immersed in DMEM for 30 seconds to solidify. After replacing the fresh culture medium, the culture medium was changed every 2-3 days. After 14 days of culture, the artificial skin was stained for live and dead cells, and images were taken using a confocal laser microscope (CLSM). In addition, a two-cell artificial skin was prepared using PKH67 to label HDFs and PKH26 to label HUVECs. After printing, the boundary between HDFs and HUVECs was found under a laser confocal microscope, and the migration of cells in the gel was observed within 3 hours and 24 hours.

[0088] The results are as follows Fig. 9 As shown in the figure, a double-cell artificial skin with a diameter of 9 mm and a height of 2.5 mm was successfully printed. Fig. 9 a). After 14 days of culture, the gel still maintained good structural integrity ( Fig. 9 b). After 3 hours of culture, the printed boundaries of HDFs and HUVECs were clearly visible, and no obvious cell migration was observed ( Fig. 9 c). However, after 24 hours of culture, the green fluorescence-labeled HDFs began to migrate to the bottom layer, and the red fluorescence-labeled HUVECs migrated to the middle layer, causing the boundary to become blurred ( Fig. 9 d). These results indicate that there is mutual migration between different cell layers. In addition, live-dead cell staining was performed on the artificial skin after 14 days of culture to observe cell survival. The results showed that after 14 days of in vitro culture, the cell density in the gel increased significantly, which was much higher than the cell density in the cell migration image after 24 hours of culture ( Fig. 9ef), indicating that the cells in the artificial skin continued to proliferate. In addition, no obvious dead cells were observed in either the HDFs layer or the HUVECs layer, indicating that the artificial skin had a high cell survival rate. These results indicate that the bicellular artificial skin maintained good structural integrity and high cell survival rate during in vitro culture and has potential for clinical application.

[0089] Example 9: Study on Diabetes Wound Healing

[0090] 150-200g SD male rats were selected and a drug-induced diabetes model was established by a single intraperitoneal injection of 65mg / kg STZ. Adequate drinking water and feed were provided daily and the bedding was changed. After 3 weeks, a wound model with a diameter of 9 mm was established. The Control group did not receive any scaffold treatment. Hydrogel group: PCMA-Fe bioink was injected into the wound in situ and cured under ultraviolet light for 60 seconds. Scaffold group: The printed acellular scaffold was transplanted into the wound. A-skin group: The printed artificial skin was transplanted into the wound. A wound model was established in healthy rats without diabetes as a control. All groups used 3M transparent dressings when fixing the wound. The 3M transparent dressing fell off on its own during the subsequent feeding period and was not replenished. The Control group had obvious infection in the wound within 7-10 days. To avoid death due to severe infection, all groups of rats were disinfected with iodine cotton balls. The wounds were photographed on days 0, 4, 7, 10, and 15 and organized into 2 cm × 2 cm images to observe the healing of the wounds over time.

[0091] The results are as follows Fig.10 As shown in the figure, compared with the acute wound control group, the diabetic control group showed significant delayed wound healing on days 4, 7, 10, and 15, which was due to the difficult-to-heal nature of diabetic wounds. The three groups treated with scaffolds had faster wound closure speeds than the control group at different time points, showing the effectiveness of scaffold treatment. Compared with the Scaffold group, the cell-loaded A-skin group showed faster healing speed and better healing degree during wound healing, highlighting the potential advantages of cell-loaded artificial skin in the treatment of diabetic wounds. Compared with the in situ cured Hydrogel, the Scaffold group showed better effects, which may be due to the fact that the micropores of the scaffold further accelerated the exchange of nutrients and the transport of oxygen, while reducing the photoinitiator residues after in situ curing and removing the free radicals generated during the photocuring process. In summary, the scaffold and cell-loaded artificial skin based on PCMA-Fe bioink have a significant promoting effect on the treatment of diabetic wounds, providing an innovative treatment strategy for wound treatment in diabetic patients.

[0092] In summary, the present invention provides a Fe for DLP 3D printing. 3+ Coordinated photosensitive collagen bio-ink, preparation method and application, the bio-ink comprises the following components: 0.5% to 1.5% m / v methacryloyl collagen solution, 0.1% to 0.5% m / v photoinitiator, 0% to 1.0% m / v ultraviolet absorber and 0.005-0.5 mg / mL Fe 3+ Solution, the bio-ink has good fluidity, stronger mechanical properties, lower swelling ratio, better anti-degradation performance; it also has the ability to promote cell migration, the performance of promoting cell proliferation, good biocompatibility, and precise printing; the PCMA-Fe bio-ink prepared by adding angiogenic polypeptide to the bio-ink of the present invention has excellent printability and precision, stronger biological activity, higher biocompatibility, and high cell survival rate; HUVECs cells are encapsulated in PCMA-Fe bio-ink for printing, which can effectively promote the proliferation, migration, and adhesion of HUVECs cells in the gel, and enhance the expression of angiogenesis-related factors (such as VEGF, vWF, CDH5, etc.), accelerate the speed of HUVECs forming blood vessels, and help HUVECs form a stable vascular network. The artificial skin prepared by the PCMA-Fe bio-ink loaded with HUVECs cells, after 14 days of culture, the gel still maintains good structural integrity, can promote cell proliferation, and has a high cell survival rate. It is applied to the treatment of diabetic wounds, which can promote wound healing, has excellent therapeutic effects, and has good clinical application potential.

Claims

1. A Fe for DLP 3D printing 3+ The coordinated photosensitive collagen bio-ink is characterized by: The bio-ink comprises the following components: 0.5% to 1.5% m / v methacryloyl collagen solution, 0.1% to 0.5% m / v photoinitiator, 0% to 0.5% m / v UV absorber and 0.005-0.5 mg / mL Fe 3+ Solution.

2. The bio-ink according to claim 1, characterized in that: The collagen is bovine collagen.

3. The bio-ink according to claim 2, characterized in that: The bovine collagen is type I bovine collagen, and / or type II bovine collagen, and / or type II bovine collagen.

4. The bio-ink according to claim 1, characterized in that: The photoinitiator includes one or more of LAP, TPO and I2959.

5. The bio-ink according to claim 1, characterized in that: The ultraviolet absorber includes one or more of lemon yellow and food coloring brilliant blue.

6. The method for preparing the biological ink according to any one of claims 1 to 5, characterized in that: The steps include: (1) dissolving freeze-dried collagen sponge in acetic acid solution to prepare collagen solution, and slowly stirring to dissolve; (2) adding methacrylic anhydride dropwise to the collagen solution obtained in step (1), adjusting the pH to 4-7, reacting at low temperature for 24 hours, dialyzing, and freeze-drying to obtain methacryloyl collagen (CMA); (3) Prepare 0.5% to 1.5% m / v methacrylated collagen solution with acetic acid solution, add sodium hydroxide solution to adjust the pH of the solution to neutral, add 0.1% to 0.5% m / v photoinitiator, 0% to 0.5% m / v UV absorber and 0.005-0.5 mg / mL Fe 3+ The solution was mixed evenly and centrifuged to remove bubbles to obtain CMA / Fe 3+ Bio-ink.

7. Use of the bio-ink as described in any one of claims 1 to 6 in the preparation of artificial skin, artificial blood vessels, cartilage and bone repair materials, corneal transplant materials, hemostatic materials, drug sustained release, drug delivery, tissue engineering and wound dressings.

8. A dressing for treating diabetic wounds, characterized in that: The dressing is obtained by adding active ingredients to the biological ink described in any one of claims 1 to 5 and printing it through DLP 3D printing.

9. Use of the dressing according to any one of claim 8 in treating diabetic wounds.

Citation Information

Patent Citations

  • A hypoallergenic, anti-aging yak collagen composition and its application

    CN113520900B